The Effectiveness of SQ4R Model on Arabic Reading Skills: A Quasi-Experimental Study at an Indonesian Islamic High School - Shery Fara Afifah; Danial Hilmi; Abdul Basid (Abjadia : International Journal of Education, 2026)
This study aims to determine the effectiveness of using the SQ4R learning model on the reading skills of students at MAN 2 Ponorogo. This study uses a Quasi Experimental Design with a Non-equivalent Control Group Design. The total sample consisted of 54 students and divided into two groups: an experimental group and a control group, each consisting of 27 students. Data collection was conducted through pretests and posttests. The results showed that the average pretest and posttest scores for the control group were 51.11 and 64.44, respectively, while those for the experimental group were 48.88 and 77.40. The experimental group’s N-Gain score of 60.6% (classified as moderately effective) was higher than the control group’s score of 27.4% (classified as ineffective). The results of the Independent Sample T-Test showed a significance value of 0.000 (< 0.05), indicating a significant difference between the two groups. The study concludes that the SQ4R learning model proved to be more effective than conventional learning in improving the Arabic reading skills of 11th-grade students at MAN 2 Ponorogo